RAGAM BAHASA WARIA DALAM SINETRON (SHEMALE LANGUAGE VARIETIES IN SOAP OPERAS) - M. Rafiek M. Rafiek (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2013)
AbstractShemale Language Varieties in Soap Operas. This study aims to describe and explainthe classification, word formation system, and varieties of language functionstransvestites in private television soap operas in Indonesia. This study uses definitionsof regional variations in sociolinguistics theories and methods of qualitative description.An analysis using the rules of grammar formation transvestite varieties of languageused refers to the rules that have been applied by Oetomo (1988) and Oetomo (2003).The results of this study were 24 classifications, 10 word formation systems, and 2functions in varieties of languages transsexual private television soap operas inIndonesia.Keywords: shemale language, classifications, word formation procedures, and functionsAbstrakRagam Bahasa Waria dalam Sinetron. Penelitian ini bertujuan untuk mendeskripsikandan menjelaskan tentang klasifikasi, tata bentukan kata, dan fungsi ragam bahasawaria dalam sinetron di televisi swasta Indonesia. Penelitian ini menggunakan ancanganteori ragam bahasa dalam sosiolinguistik dan metode deskriptif kualitatif. Teknik analisisdata menggunakan kaidah tata bentukan ragam bahasa waria yang digunakan mengacupada kaidah yang telah diterapkan oleh Oetomo (1988) dan Oetomo (2003). Hasilpenelitian ini adalah 24 klasifikasi, 10 tata bentukan kata, dan 2 fungsi ragam bahasawaria dalam sinetron di televisi swasta Indonesia.Kata-kata kunci: bahasa waria, klasifikasi, tata bentukan kata, dan fungsi